Chile's Growth and Development : Leadership, Policy-Making Process, Policies, and Results - Schmidt-Hebbel, Klaus (World Bank, Washington, DC, 2017)
This paper analyzes the relations between leadership, the policy making process, policies and institutions, and development results in Chile. It starts with a stylized model for the dynamics of development that derives a Kuznets type relation between growth and distribution of income, determined by the quality of leadership, the policy making process, institutions, and policies. This framework is applied to Chile, identifying the features of the policy making process and leadership that allowed for continuation of growth enhancing reform, with a stronger focus on equity goals, since the transition to democracy. As a result of three decades of reforms, Chile has recorded a quantum leap in economic growth, which is traced down to specific reforms. Yet Chile's equity experience is much more mixed: poverty has declined massively but income remains highly concentrated, a likely result of shortcomings in the quality of education and in labor markets. The paper reviews the major risks to the country's future development pace and points out the main reform challenges faced by policy makers.